Intratumoral Nanofluidic System for Enhancing Tumor Biodistribution of Agonist CD40 Antibody. Issue 10 (9th July 2020) - Chua, Corrine Ying Xuan; Ho, Jeremy; Susnjar, Antonia; Lolli, Graziano; Di Trani, Nicola; Pesaresi, Federica; Zhang, Mengying; Nance, Elizabeth; Grattoni, Alessandro
Abstract: Tumor uptake and biodistribution of immunotherapy is associated with clinical response as well as toxicity. To augment immunotherapy bioavailability in the tumor, an intratumoral administration route via direct injection or local release technologies has emerged as an appealing approach. Here the biodistribution of an agonistic anti‐CD40 monocolonal antibody (CD40 mAb) when sustainably delivered via an intratumoral nanofluidic drug‐eluting seed (NDES) is evaluated in comparison to systemic or direct intratumoral administration. The NDES achieves sustained drug release through diffusion by leveraging electrostatic nanoconfinement within nanochannels, without requiring internal or external actuation. Using the 4T1 murine mammary carcinoma model, the biodistribution of Alexa Fluor‐700 conjugated CD40 mAb is tracked via fluorescence imaging analysis, comparing three routes of administration over 7 and 14 days. NDES‐treated cohort shows sustained high levels of intratumoral CD40 mAb without off‐target organ exposure, compared to the intraperitoneal and direct intratumoral administration. Moreover, radiation pre‐treatment of the 4T1 tumors augments tumor retention of CD40 mAb in the NDES group. Overall, sustained intratumoral release of CD40 mAb via the NDES improves local drug bioavailability without systemic dissemination, suggesting an enhanced approach for immunotherapy administration. Abstract : The nanofluidic drug‐eluting seed is an intratumoral implant for sustained drug release locally. In comparison to systemic or direct intratumoral administration, the drug is confined locally, thus minimizing off‐target organ or systemic distribution. Through constant and sustained release controlled by a nanofluidic membrane, the need for repeated interventions is obviated.